2012
DOI: 10.1161/strokeaha.111.635250
|View full text |Cite
|
Sign up to set email alerts
|

A Rat Model of Studying Tissue-Type Plasminogen Activator Thrombolysis in Ischemic Stroke With Diabetes

Abstract: Background and Purpose Post-stroke hyperglycemia and diabetes mellitus are associated with lower thrombolytic efficacy and an increased risk of post-ischemic cerebral hemorrhage. We aimed to develop a rodent model of thrombolysis in diabetic stroke that mimics the clinical situation. Method Male 6 weeks type I diabetic rats (14 weeks old) rats were subjected to embolic focal stroke and treated with tPA at 1.5 hours. Reperfusion and 24-hour neurological outcomes were measured and compared to non-diabetic cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 18 publications
1
61
1
Order By: Relevance
“…Ischemic stroke results in long-term disability and is a leading cause of mortality in developed countries (1,2). Early reperfusion is the most effective therapy for acute brain ischemia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ischemic stroke results in long-term disability and is a leading cause of mortality in developed countries (1,2). Early reperfusion is the most effective therapy for acute brain ischemia.…”
Section: Introductionmentioning
confidence: 99%
“…Brain edema, traditionally classified as vasogenic and cytotoxic edema, serves a critical role in cerebral I/R injury (1,2,7). Cytotoxic edema occurs due to increased water permeability of cell membranes, which is associated with the aquaporin family, a group of selective water transport membrane proteins (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that hyperglycemia combined with cerebral ischemia-reperfusion model induces and exacerbates oxidative stress and poor reperfusion in the microcirculation of brain. 36,37 We previously reported that a high colloidal dispersion stability and biocompatibility of RNP improved a blood circulation for extended period.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin resistance is commonly present in patients with T2DM, hypertensive patients, elderly and obese populations, and in patients suffering from other vascular diseases 101. In T1DM rats subject to stroke, treatment with tPA increased brain hemorrhage, BBB permeability, and failed to improve neurological functional outcome while increasing inflammatory responses 102, 103. Another study reported that hyperglycemia during tPA infusion after stroke in rats increased BBB permeability and intracerebral hemorrhage, which may be mediated by oxidative stress mechanisms such as increasing superoxide production by nicotinamide adenine dinucleotide phosphate oxidase 104.…”
Section: Mechanisms Of Ischemia/reperfusion Damage In Diabetic Strokementioning
confidence: 99%